Implementasi Digital Marketing Pada PT Yuk Bersihin Sejahtera Menurut Perspektif Syariah - Susanto, Apip; Yunita, Patria; Syafiudin , Ahmad (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2024)
PT Yuk Bersihin Sejahtera is a service company operating in the cleaning sector in Jakarta. PT Yuk Bersihin Sejahtera has a vision to offer opportunities to young high school/vocational school graduates who wish to continue their education to college independently. PT Yuk Bersihin Sejahtera has a mission to provide the best cleaning services because every community has the right to a clean and healthy life. This research aims to determine the implementation of digital marketing implemented by PT Yuk Bersihin Sejahtera according to a sharia perspective. Recognizing market characteristics and competitors is very necessary for companies to remain competitive and survive. In this research, descriptive qualitative research was used with the type of field research. The data in this research was obtained from interviews, observations and documentation, then the data was processed by editing, describing and categorizing and then analyzed in depth. The results of this research, PT Yuk Bersihin Seajahtera has implemented a marketing strategy with the Digital Marketing concept in accordance with a sharia perspective. Starting from the basic philosophical concept that marketer activities do not conflict with sharia. Marketing ethics from marketers avoid lies. The approach with consumers is carried out in accordance with sharia, proven by treating consumers as equal partners. The perspective of competitors makes competitors become partners in the successful implementation of sharia economics. A work culture that is in accordance with sharia by prioritizing honesty and intelligence in marketing products and services to consumers.